Tinjauan Singkat Adversity Quotient - Lasmono, Hari K. (Faculty of Psychology, Universitas Surabaya, 2001)
The advantage of adversity quotient (AQ) over intelligence quotient (IQ) and emotional quotient (EQ) are discussed through a brief explanation of the essence of AQ and levels of adversities, which comprises the societal, the workplace, and the individual adversities. The building blocks of AQ i.e. cognitive psychology, neurophysiology, and psychoneuroimmunology are also explained. A brief expose of the continuum of AQ and techniques to enhance AQ are also discussed. Keunggulan adversity quotient (AQ) terhadap intelligence quotient (IQ) dan emotional quotient (EQ) dibahas melalui uraian hakikat AQ dan tingkatan adversity yang terdiri atas societal adversity, workplace adversity, dan individual adversity. Juga dikemukakan teori-teori pendukungnya yang meliputi psikologi kognitif, neurofisiologi, dan psikoneuroimmunologi. Kontinum AQ dan teknik meningkatkan AQ juga disinggung sepintas.